The Contribution of GHRM and Green Innovation to Environmental Performance at Pt. Indonesian Air & Marine Supply - Rahmat, Rahmat; Rumambi , Freddy J. (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to explore the relationship between Green Human Resource Management (GHRM), Green Innovation, and Environmental Performance at PT. Indonesian Air & Marine Supply. The study population consisted of 100 employees from the company’s shipping department. The purposive sampling method was used to select 80 respondents who had been employed for at least two years and were directly involved in the shipping field. The analysis results indicate that the implementation of GHRM and Green Innovation significantly influences Environmental Performance at PT. Indonesian Air & Marine Supply. Recommendations for company management include increasing investment in GHRM and Green Innovation, as well as enhancing the integration between these two factors to achieve better environmental sustainability goals.